Hur påverkar mekaniskt snytbaggeskydd, markberedning, plantstorlek och plantgödsling granplantors överlevnad och tillväxt? - Abrahamsson, Johanna; Wallgren, Jessica (2022)
Reforestation of land entails both costs and uncertainties. Risk of pine weevil infestation, competition from other vegetation, frost and insufficient nutrient supply are some examples. The completed study has therefore investigated how mechanical pine weevil protection, plant size, soil preparation and plant fertilization can affect survival and continued growth during the first two years after planting. The effects of coating protection on growth have also been followed up, as well as the extent to which plants treated with woodcoat can assimilate manure. The hypotheses in the study were that larger plants would survive and grow better than the smaller ones. At the same time, would mechanical pine weevil protection and soil preparation lead to improved plant survival. Plant fertilization was also predicted to lead to a positive effect on continued growth. A planting experiment was established in Västerbotten's coastal region in the autumn of 2018 and 18 different experimental stages were tested. Inventory was carried out in the spring and autumn of 2019 and the autumn of 2020. Thereafter, the data material was processed and analysed in Excel and Minitab.